2021
DOI: 10.3390/s21020453
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tri-Axial Piezoelectric MEMS Accelerometer with Folded Beams

Abstract: Microelectromechanical (MEMS) piezoelectric accelerometers are diversely used in consumer electronics and handheld devices due to their low power consumption as well as simple reading circuit and good dynamic performance. In this paper, a tri-axial piezoelectric accelerometer with folded beams is presented. The four beam suspensions are located at two sides of the mass aligned with edges of the mass, and the thickness of the beams is the same as the thickness of the mass block. In order to realize the multi-ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…MEMS accelerometers can be classified based on their principles of operation, including capacitive [ 9 , 18 ], piezoresistive, resonant [ 19 , 20 ], and piezoelectric types [ 21 , 22 , 23 , 24 ]. Piezoelectric MEMS accelerometers exhibit several advantages over other types, including a wider operating frequency range, along with low power consumption, low-temperature dependence, and high sensitivity [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…MEMS accelerometers can be classified based on their principles of operation, including capacitive [ 9 , 18 ], piezoresistive, resonant [ 19 , 20 ], and piezoelectric types [ 21 , 22 , 23 , 24 ]. Piezoelectric MEMS accelerometers exhibit several advantages over other types, including a wider operating frequency range, along with low power consumption, low-temperature dependence, and high sensitivity [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The small size, low power consumption, and low cost of these micromachined sensors make these sensors an excellent alternative to the traditional macroscale inertial sensors. The function of MEMS accelerometers is generally based on different transduction principles such as electrostatic [5,6], piezoelectric [7], piezoresistive [8], and optical [9]. Among these, capacitive MEMS accelerometers are most widely used for different applications, owing to their relatively high dynamic range, small size, and low cost [10].…”
Section: Introductionmentioning
confidence: 99%
“…In AlN-based BAW resonators and high-frequency filters, out-of-plane (110)-orientated Mo thin films are typically used as bottom electrodes because the (110) texture of the Mo films enables the growth of highly c -axis (0001) crystal orientated AlN active layers, which are required for achieving the highest piezoelectric constant and electroacoustic coupling. It was revealed that the growth of (0001)-orientated AlN on (110)-textured Mo (or vice versa ) is possible thanks to the presence of the local heteroepitaxial relationship of AlN(0001)­[21̅1̅0]||Mo(110)[1̅11] with a small lattice mismatch of 4.9% and the effective reduction of the crystallization energy. , The degree of the c -axis (0001) crystal orientation in the AlN growth crucially depends on the quality of the (110)-texturing and the surface morphology of the Mo bottom electrode. Sputtering or physical vapor deposition is the most frequently used method to deposit Mo thin films with resistivities lower than 10 –6 Ω m, which are normally required to reduce the ohmic loss . Although some reported improved (110)-textures in Mo films by adjusting the working pressure, the discharge power, and the deposition rates in magnetron sputtering, the thickness of the Mo bottom electrodes typically needs to be a few hundred nanometers (e.g., ∼200–300 nm) to achieve a high degree (110)-texture evolution. , This may pose a serious challenge for further development of the AlN-based BAW technology, as the resonance frequency of a BAW device is inversely proportional to the thickness of the AlN layer and its (top and bottom) electrodes .…”
Section: Introductionmentioning
confidence: 99%